Surfactant-assisted mild solvothermal synthesis of nanostructured LiFePO4/C cathodes evidencing ultrafast rate capability. (20th February 2015) - Di Lupo, F.; Meligrana, G.; Gerbaldi, C.; Bodoardo, S.; Penazzi, N.
Highlights: Nanostructured LiFePO4 /C by surfactant assisted solvothermal synthesis. Novel and simple preparation method, with no critical parameters. Noticeable stability, good capacity values and capacity retention after prolonged cycling. Improved rate capability at a very high C-rate (100C). High performance for the next generation of advanced high power Li-ion batteries. Abstract: A surfactant-assisted solvothermal synthesis is hereby applied to produce carbon-coated LiFePO4 /C nanostructured Li-ion battery cathodes. The use of different mixed alcohol/water solutions for the dissolution of a cationic surfactant is absolutely peculiar in this field and herewith exploited to tailor-make the properties of the active material particles (e.g., morphology and electrochemical behaviour). Thorough investigation is carried out by means of X-ray powder diffraction, scanning and transmission electron microscopy, cyclic voltammetry and constant current charge-discharge cycling. The best performing sample, obtained in a 20:80 w/w ethanol:water solution, demonstrates good specific capacity values, high Coulombic efficiency and rate capability, with stable behaviour upon long-term cycling even at ultrafast 100C discharge regime. This is definitely remarkable for a nanosized powder specifically conceived for high power applications obtained by means of low cost raw materials, simple and reliable procedures.